Cardiac Oscillations Complicating Brain Death Diagnosis - Brittany Bolt; Farid Muakkassa; Lindsay Bruening; Cameron Marcus; Brittany Cunningham; Erin Pawlak; Richard Gandee; Christopher Newey (Case Reports in Critical Care)
Death by neurologic criteria (DNC) or brain death is a clinical diagnosis. It is often complicated by variations in policies as well as confounders on examination. We discuss here the case of a 27-year-old male who had a cardiac arrest following toxic gaseous exposure. He ultimately progressed to brain death but was identified as having cardiac oscillations during clinical assessments that complicated the diagnosis. We discuss the case as well as the maneuvers used to clarify that the “triggered breaths” on the ventilator were indeed cardiac oscillations.